Good performances but short lasting efficacy of Actellic 50 EC Indoor Residual Spraying (IRS) on malaria transmission in Benin, West Africa - Rock Aïkpon; Michel Sèzonlin; Filémon Tokponon; Mariam Okè; Olivier Oussou; Frédéric Oké-Agbo; Raymond Beach; Martin Akogbéto (Parasites & Vectors, 2014)
Abstract Background The National Malaria Control Program (NMCP) has been using pirimiphos methyl for the first time for indoor residual spraying (IRS) in Benin. The first round was a success with a significant decrease of entomological indicators of malaria transmission in the treated districts. We present the results of the entomological impact on malaria transmission. Entomologic parameters in the control area were compared with those in intervention sites. Methods Mosquito collections were carried out in three districts in the Atacora-Dongo region of which two were treated with pirimiphos methyl (Actellic 50EC) (Tanguiéta and Kouandé) and the untreated (Copargo) served as control. Anopheles gambiae s.l. populations were sampled monthly by human landing catch. In addition, window exit traps and pyrethrum spray catches were performed to assess exophagic behavior of Anopheles vectors. In the three districts, mosquito collections were organized to follow the impact of pirimiphos methyl IRS on malaria transmission and possible changes in the behavior of mosquitoes. The residual activity of pirimiphos methyl in the treated walls was also assessed using WHO bioassay test. Results A significant reduction (94.25%) in human biting rate was recorded in treated districts where an inhabitant received less than 1 bite of An. gambiae per night. During this same time, the entomological inoculation rate (EIR) dramatically declined in the treated area (99.24% reduction). We also noted a significant reduction in longevity of the vectors and an increase in exophily induced by pirimiphos methyl on An. gambiae. However, no significant impact was found on the blood feeding rate. Otherwise, the low residual activity of Actellic 50 EC, which is three months, is a disadvantage. Conclusion Pirimiphos methyl was found to be effective for IRS in Benin. However, because of the low persistence of Actellic 50EC used in this study on the treated walls, the recourse to another more residual formulation of pirimiphos methyl is required.